The explanation of the semantic dysfunction relative to the written production of the Algerian Arabic-speaking student in French in the light of the structural semantics - AZREGAINOU, Zahir (Journal of Human Sciences, 2020)
Currently, in Algeria, despite the application of the competency approach, the situation is as it is for French language.  Failure is clearly evident in the written productions of learners where teachers observe semantic dysfunction.  Structural semantics has allowed us to clarify this problem...  A central idea has emerged : the existence of meaning is based on relationship.  Each language has its semantic combinatorics.  The problem of the Algerian Arabic-speaking student is that he (she) owns that of his mother tongue and does not possess that of the French language (except in some cases).  When he / she is writing in French, he (she) is practicing a lexematic and non-sememic approach; the latter is based on the compatibility or incompatibility of semantic units.  This is what appeared in the analysis of the corpus that we chose as a sample.